Navigating the clinical landscape of artery of Percheron infarction: A systematic review - Oday Atallah; Yasser F. Almealawy; Arwa Salam Alabide; Minaam Farooq; Vivek Sanker; Suraa N. Alrubaye; Rami Darwazeh; Wireko Andrew Awuah; Toufik Abdul-Rahman; Ahmed Muthana; Aalaa Saleh; Jack Wellington; et al. (eNeurologicalSci)
Introduction: Infarction of the artery of Percheron (AOP) is a rare vascular condition where a single arterial branch supplies blood to the thalamic and midbrain regions, leading to neurological deficits. The challenge lies in its often-delayed diagnosis due to its rarity and diverse clinical presentations, necessitating heightened awareness among clinicians for expedited diagnosis and appropriate therapeutic interventions. Materials and methods: All relevant studies involving patients diagnosed with infarction of AOP were retrieved from PubMed, Google Scholar, Web of Science, and Scopus. Only human studies that were published in full English-language reports were included. Included in the search were the terms “Artery of Percheron,” “infarction,” “stroke,” and “demarcation”. Age, gender, presenting symptoms, treatment, recovery time, and outcome of patients with AOP infarction were all recorded. Results: A systematic review was conducted on a total of 530 articles, out of which 130 articles met the specified requirements. The average age is 59, with men comprising 57.7% of the population. The symptoms reported were visual disturbance in 43.9% of cases and changed mental state in 77.2% of cases. Treatment options include conservative management (85.4%), thrombolysis (11.3%), and other approaches. The optimal age range for recovery is between 41 and 50 years old. Conclusion: Our study on acute AOP infarction highlights male predominance, common comorbidities like hypertension and diabetes, and prevalent symptoms including visual disturbance and altered mental state. Early recognition is crucial, with thrombolytic therapy within the critical time window showing promising outcomes. These findings offer insights for enhanced clinical management of AOP infarction.